Statistical Analysis and Optimum Performanceof the Gas Turbine Power Plant - Thamir K., Ibrahim; M. M., Rahman; M. K., Mohamed; F., Basrawi (Universiti Malaysia Pahang, 2016)
The statistical analyses of the gas turbine power plant are presented in this paper. A novel approach for analysing gas turbine operation and performance is developed utilizing statistical modelling technology, specifically response surface methodology (RSM) which was based on the central composite design (CCD) applied. The proposed correlations have a remarkably satisfactory performance for all simulation data, where the determination coefficient (R2) about 0.985. Moreover, the newly developed correlations were validated with the real data from the gas turbine of MARAFIQ CCGT power plant. Moreover, the newly developed correlations were validated with the real data from the GT units in the MARAFIQ CCGT power plant. The error analysis was applying to approximation the error (1.123% of the GT plants). From applied the ANFIS technique, the optimum thermal efficiency was about 56% with the effect of the pressure ratio and compressor isentropic efficiency